2014
DOI: 10.1088/0953-8984/27/3/032101
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial ionic ‘liquids’: connecting static and dynamic structures

Abstract: It is well known that room temperature ionic liquids (RTILs) often adopt a charge-separated layered structure, i.e. with alternating cation- and anion-rich layers, at electrified interfaces. However, the dynamic response of the layered structure to temporal variations in applied potential is not well understood. We used in situ, real-time x-ray reflectivity to study the potential-dependent electric double layer (EDL) structure of an imidazolium-based RTIL on charged epitaxial graphene during potential cycling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 55 publications
6
74
1
Order By: Relevance
“…The addition of 100 mM [BMIM] + to the N 2 -saturated MeCN containing 0.1 M TBAPF6 ( Figure 5, left) causes an increase of charge stored within the double layer region [29,30], which may be presumed to be due to the adsorption of [BMIM] + at the electrode/electrolyte interface of the negatively polarized CuSn film [31][32][33]. Similar phenomena have been observed for Au electrodes [34][35][36][37], and it has been demonstrated that [Im] + cations prefer to π-stack and lie flat on electrode surfaces, thereby supporting more capacitive charge build-up than an inner layer containing large TBA + cations [38][39][40].…”
Section: Adsorption Pre-catalysis Peaksupporting
confidence: 61%
“…The addition of 100 mM [BMIM] + to the N 2 -saturated MeCN containing 0.1 M TBAPF6 ( Figure 5, left) causes an increase of charge stored within the double layer region [29,30], which may be presumed to be due to the adsorption of [BMIM] + at the electrode/electrolyte interface of the negatively polarized CuSn film [31][32][33]. Similar phenomena have been observed for Au electrodes [34][35][36][37], and it has been demonstrated that [Im] + cations prefer to π-stack and lie flat on electrode surfaces, thereby supporting more capacitive charge build-up than an inner layer containing large TBA + cations [38][39][40].…”
Section: Adsorption Pre-catalysis Peaksupporting
confidence: 61%
“…This is the first time the degree of ion ordering can be directly visualized and analyzed through imaging techniques with a lateral resolution of around 20 nm. This will allow for comparison of the AFM result with X-ray and neutron scattering techniques performed on similar systems in the future [16,38]. All the dislocations marked in Regions I-III show the same general behavior but it happens over different lengths scales between 50 and 80 nm.…”
Section: Resultsmentioning
confidence: 90%
“…Time resolved experiments, covering the relaxation dynamics on the seconds to minute scale, indicated the presence of ultraslow interfacial processes. 31,32 Scanning tunneling microscopy and AFM studies indicate that the substrate-adsorbed cation layer is affected by an applied potential. 20,28,[33][34][35] Sum frequency generation (SFG) spectroscopy 36 detected molecular reorientations upon variation of the applied potential.…”
Section: Introductionmentioning
confidence: 99%